Femtosecond Laser-Colorized ITO Films for Blue Light Attenuation and Image Screening - Tseng, Ya-Hsin; Yang, Hung; Luo, Chih-Wei (My University, 2018)
Laser-colorized ITO films are fabricated using femtosecond laser annealing. The fluence-dependent nanostructures on ITO significantly attenuate blue light, which are suited to eye protection and the screening of images behind ITO for information security.